Style in Jakarta Post Editorial - Faiza Hawa; Ajeng Setyorini (ETERNAL (English Teaching Journal), 2017)
The objectives of the study is to find out whether the writers’ articles of the Jakarta Post issued in January 2015 have good style in their writing or not and to find out the element of  style used in Jakarta Post articles issued on January 2015. The subject of the study is the Jakarta Post Issued  in January 2015. There are five editorials selected and then analyzed based on Seyler’s theory. Based on the analysis, the editorials applied formal words. From the analysis, it was found that the total sentence for simple sentence is 34, 14 compound sentences, 24 complex sentences, 24 expanded sentences, 2 antithesis, and 1 metaphor.  In organizating the text, the writer of the editorial placed the main topic in the beginning paragraph. A writer can make good style in his/her writing by applying more active sentences in his/her writing, use familiar words and not using cliché, use short sentences, and write with nouns and verbs.